Change Blindness in a Dynamic Scene Due to Endogenous Override of Exogenous Attentional Cues. (August 2013) - Smith, Tim J; Lamont, Peter; Henderson, John M
Change blindness is a failure to detect changes if the change occurs during a mask or distraction. Without distraction, it is assumed that the visual transients associated with the change will automatically capture attention ( exogenous control), leading to detection. However, visual transients are a defining feature of naturalistic dynamic scenes. Are artificial distractions needed to hide changes to a dynamic scene? Do the temporal demands of the scene instead lead to greater endogenous control that may result in viewers missing a change in plain sight? In the present study we pitted endogenous and exogenous factors against each other during a card trick. Complete change blindness was demonstrated even when a salient highlight was inserted coincident with the change. These results indicate strong endogenous control of attention during dynamic scene viewing and its ability to override exogenous influences even when it is to the detriment of accurate scene representation.